The electrical properties of graphene modified by bromophenyl groups derived from a diazonium compound - Dong, Xiaochen (2013)
Graphene field-effect transistors were fabricated with mechanically exfoliated single-layer graphene (SLG) and bilayer graphene (BLG) sheets and the functionalization effects of bromophenyl groups derived from a diazonium compound on its transfer properties were explored. Spectroscopic and electrical studies reveal that the bromophenyl grafting imposes p-doping to both SLG and BLG. The modification of SLG by bromophenyl groups significantly reduces the hole carrier mobility and the saturation current in SLG transistors, suggesting an increase in both long-range impurity and short-range defect scattering. Unexpectedly, the bromophenyl group functionalization on BLG does not obviously increase both types of scattering, indicating that the BLG is relatively more resistant to charge- or defect-induced scattering. The results indicate that chemical modification is a simple approach to tailor the electrical properties of graphene sheets with different numbers of layers.